Experimental determination of edge forces in carving using a novel device - Lüthi, A.; Rhyner, H.; Germann, R.; Marthy, R.; Staudenmann, M. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Deformation and movement of a carving ski are determined by its construction and the external forces acting on the ski. Whereas the forces exerted from the skier to the ski have been determined experimentally, the forces building up between ski and snow have so far only been determined numerically [1,2]. The main purpose of the current work was to bridge this gap with a laboratory device which allows to determine the forces on the carving edge in function of snow properties, edging angle, ski load and finally but not last the ski construction and the used bindings and plates.